2023
DOI: 10.3390/ijms24076721
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Barrier Maintenance, and Gut Microbiome Modulation Effects of Saccharomyces cerevisiae QHNLD8L1 on DSS-Induced Ulcerative Colitis in Mice

Abstract: The use of probiotics has been considered as a new therapy option for ulcerative colitis (UC), and yeast has recently received widespread recommendation for human health. In this study, the probiotic characteristics of four yeast strains, Saccharomyces boulardii CNCMI-745, Kluyveromyces marxianus QHBYC4L2, Saccharomyces cerevisiae QHNLD8L1, and Debaryomyces hansenii QSCLS6L3, were evaluated in vitro; their ability to ameliorate dextran sulfate sodium (DSS)-induced colitis was investigated. Among these, S. cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…YE treatment recovered the pathological and abnormal morphological changes of colon tissues, reduced the levels of LPS and D-LA in serum, and up-regulated ZO-1 and Occludin. Our finding was in accordance with recent research that showed saccharomyces cerevisiae QHNLD8L1 alleviated the dextran sulfate sodium-induced colitis in mice by modulating specific microbiota, increasing SCFA production, and enhancing the gut barrier [80] .…”
Section: Discussionsupporting
confidence: 93%
“…YE treatment recovered the pathological and abnormal morphological changes of colon tissues, reduced the levels of LPS and D-LA in serum, and up-regulated ZO-1 and Occludin. Our finding was in accordance with recent research that showed saccharomyces cerevisiae QHNLD8L1 alleviated the dextran sulfate sodium-induced colitis in mice by modulating specific microbiota, increasing SCFA production, and enhancing the gut barrier [80] .…”
Section: Discussionsupporting
confidence: 93%
“…are novel species of potential beneficial microorganism productors of SCFAs. Additionally, Facecalibaculum contributes to reducing colon inflammation by stimulating Treg cells [ 62 ]. These results suggest that synbiotic maternal supplementation during gestation and lactation boosts the colonization of the offspring gut during suckling.…”
Section: Discussionmentioning
confidence: 99%
“…As a potential probiotic bacterium, its species has potential therapeutic effects in metabolic, inflammatory, and neoplastic diseases [28][29][30][31]. The upregulation of Butyricimonas abundance can enhance the function of fatty acid biosynthesis, increase the production of SCFAs, and promote the synthesis of butyrate [32]. Recent studies have found that Phocaeicola strains can help maintain the epithelial barrier by regulating cytokine levels and the secretion of SCFAs, thereby improving dextran sodium sulfate-induced colitis in mice [33].…”
Section: Discussionmentioning
confidence: 99%